2022
DOI: 10.1172/jci140685
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-produced VEGFC is induced by efferocytosis to ameliorate cardiac injury and inflammation

Abstract: Clearance of dying cells by efferocytosis is necessary for cardiac repair after myocardial infarction (MI). Recent reports have suggested a protective role for vascular endothelial growth factor C (VEGFC) during acute cardiac lymphangiogenesis post MI. Here we report that defective efferocytosis by macrophages after experimental MI leads to a reduction in cardiac lymphangiogenesis and Vegfc expression. Cell-intrinsic evidence for efferocytic-induction of Vegfc was revealed after adding apoptotic cells to cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 51 publications
4
67
0
Order By: Relevance
“…In line with my findings that vegfc is expressed in cECs during cardiac regeneration in zebrafish, a previous study revealed that Vegfc is expressed in ECs in neonatal mice after cardiac injury, further confirming that Vegfc acts as an angiocrine following cardiac injury in regenerative settings (Quaife-Ryan et al, 2017). On the other hand, it has been very recently reported that macrophages are a source of VEGFC following cardiac injury in adult mice (Glinton et al, 2022). It would be interesting to investigate if VEGFC from different cellular sources contribute to a pleiotropic role to promote cardiac regeneration following injury.…”
Section: Vegfc Is An Angiocrine Required For Cardiac Regeneration Ind...supporting
confidence: 81%
“…In line with my findings that vegfc is expressed in cECs during cardiac regeneration in zebrafish, a previous study revealed that Vegfc is expressed in ECs in neonatal mice after cardiac injury, further confirming that Vegfc acts as an angiocrine following cardiac injury in regenerative settings (Quaife-Ryan et al, 2017). On the other hand, it has been very recently reported that macrophages are a source of VEGFC following cardiac injury in adult mice (Glinton et al, 2022). It would be interesting to investigate if VEGFC from different cellular sources contribute to a pleiotropic role to promote cardiac regeneration following injury.…”
Section: Vegfc Is An Angiocrine Required For Cardiac Regeneration Ind...supporting
confidence: 81%
“…In further support of a role of monocytes/macrophages in promoting LM progression, we found that the blockade of their recruitment or differentiation using anti-CSF1R or anti-CCL2/MCP1 antibodies inhibited Pik3ca -driven lymphatic overgrowth. Although our study did not assess a causal link between macrophage recruitment, VEGF-C production, and lymphangiogenesis in a wild-type setting, previous studies in different disease contexts have established such links ( Schoppmann et al, 2002 ; Alishekevitz et al, 2016 ; Glinton et al, 2022 ; Kataru et al, 2009 ). Of note, the recruited macrophages may additionally produce factors that promote proteolytic processing of, or synergize with VEGF-C, to enhance its lymphangiogenic activity ( Jha et al, 2017 ).…”
Section: Discussionmentioning
confidence: 90%
“…It has been proposed that VEGF-C represents the core regulator for inducing tumor lymphangiogenesis ( 32 ). Accordingly, we analyzed whether hnRNPA1 participates in regulating VEGF-C to promote the lymphangiogenesis of PDAC.…”
Section: Resultsmentioning
confidence: 99%